Do financial signals matter? The influence of profitability, stock price, and dividend policy on investment decisions in Indonesian manufacturing firms - Puspitae, Zeri; Zulaika, Tatik; Rahmiati, Rahmiati; Fransiska, Christina; Angela, Leliana Maria (Universitas Muhammadiyah Yogyakarta, Indonesia, 2025)
Research aims: This study aims to determine investment decisions made by investors based on the performance of manufacturing companies listed on the Indonesia Stock Exchange in 2018-2021 based on an analysis of the influence of financial ratios.Design/Methodology/Approach: Profitability, stock price, and dividend policy ratios were employed in this analysis. This study employed a quantitative approach and relied on the usage of secondary data sources in the form of yearly reports to compile its findings. This research used a purposive sampling population of manufacturing companies listed on the IDX in 2018-2021.Research findings: The results of this study state that profitability does not affect investment decisions because companies employ profits generated in certain periods for other things, such as paying debts and distributing dividends. While the stock price has a positive and significant effect on investment decisions, the higher the stock price, the higher investor confidence in the company. This applies because the dividend policy is considered by investors, and the company has a responsibility to fulfill its obligations for the funds that investors have invested.Theoretical contribution/ Originality: This research contributes to signal theory, which states that every corporate action related to a company has the potential to produce information content as a signal. Information released as an announcement will give signals to investors to make investment decisions. Investors need information because it paints a picture of the company's history, its current state, and the effect the market crisis is having on its future.Practitioner/Policy implication: This research is expected to be useful as additional information for companies and investors. It canResearch limitation/Implication: For investors, they should pay attention to other aspects of the risk company's performance that are generally disclosed, for example the company's capital structure obtained from debt, the company's ability to pay taxes.